Blended Learning Method Based on Quipper School to Improve Concepts Understanding and Independence Learning (Universitas Negeri Semarang, 2018)
The purpose of this research is to know the effectiveness of blended learning method based on quipper school media in order to improve students understanding of the concept and their independece learning in science learning. The research method used is quasi experiment with nonequivalent pretest-posttest control group design. The data collected using observation techniques and tests. The population in this research is all students of class VIII SMPN 1 Sumowono consists of 193 students. Samples were taken using purposive sampling technique. Class VIII D is selected as the experimental class, while class VIII F is selected as the control class. The results showed that: (1) classical accomplishment of experimental class increased by 28.13% and control class increased by 15.62%. This suggests that there is an increase in the students' understanding of the concept of experimental class on the medium criterion, while the control class on low criterion; (2) Learning independence of experimental class is 76.78% and is in self-supporting category. The conclusion of this research is that the blend learning method based on Quipper School is effective to improve the students’ understanding of the concept and their learning independence of the students. Blend learning method based on Quipper School is expected to be a reference to be applied in learning